Water Resources Management Innovative and Green Solutions. - Brears, Robert C. (De Gruyter STEM, 2021)
Water resource management consists of planning, developing, distributing and managing the available water resources. With increasing urbanization, optimized water management becomes more demanding. This book presents innovative solutions for present as well as future challenges we are facing in water conservation, recycling and reuse.